(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
The Spree-Neisse-Bober Euroregion was established on the Polish and German borderland on September 21, 1993. The statutes, principles of co-operation, aims and tasks were elaborated. In the last seven years a number of investment projects have been carried out: the construction of a sewage treatment plant Gubin - Guben, a number of cross? border projects (founding the Landscape Park Krzesin -Neuzelle, sanctuaries of Nature, ecological grounds). One of the goals of the Spree-Neisse-Bober Euroregion " is to level the existing economic differences between Poland and Germany and to co-operate in the fields of culture, tourism, sports, education and mass media.